Peningkatan Literasi Kesehatan Gigi pada Pekerja Migran Indonesia di Taiwan - Yusra, Yohana; Putri, Christy Anandha; Rinanti, Astri; Ariani, Ariani (Universitas Prof. Dr. Moestopo (Beragama), 2026)
Dental caries and periodontal disease remain highly prevalent in Indonesia and are closely related to low oral health literacy and suboptimal preventive behaviors. Indonesian migrant workers face additional barriers to accessing dental care, including language constraints, long working hours, and limited information on insurance-covered services. This community-based service program aimed to improve oral health literacy and facilitate early detection of dental problems among Indonesian migrant workers in Taiwan through an integrated “Screen–Teach–Refer” model with local diaspora organizations. Activities included needs assessment with community leaders, intraoral examination using the DMF-T index, structured education on caries prevention, fluoride use, toothbrushing techniques, sugar intake, and the importance of six-monthly dental visits, as well as demonstration and guided practice of proper toothbrushing and information on NHI dental clinics. The program reached adult migrant workers, enabled on-site detection of untreated caries and missing teeth, and prompted active participation in education sessions. Preliminary responses suggest improved understanding of daily preventive practices and available NHI-covered dental services.